Seascapes as drivers of herbivore assemblages in coral reef ecosystems. Issue 1 (7th November 2018) - Roff, George; Bejarano, Sonia; Priest, Mark; Marshell, Alyssa; Chollett, Iliana; Steneck, Robert S.; Doropoulos, Christopher; Golbuu, Yimnang; Mumby, Peter J.
Abstract: Notionally herbivorous fishes maintains a critical ecosystem function on coral reefs by grazing algae and maintaining highly productive algal turf assemblages. Current paradigms implicate habitat complexity, predation, and primary productivity as major drivers of the distribution and abundance of herbivorous fish, yet little is known about the relative contribution of these factors. Here, we compare bottom‐up and top‐down drivers of notional herbivore assemblages across an environmental gradient of wave exposure in the Palau archipelago. We surveyed herbivore assemblages at reef slopes (6–9 m) across 18 sites, and quantified proxies of top‐down control (predator biomass, habitat complexity) and bottom‐up drivers (net primary production, nutrients) at each site. Despite substantial variability in herbivore biomass throughout the archipelago (6–65 g/m 2 ), general additive models indicate that neither top‐down nor bottom‐up drivers significantly predicted biomass or density of herbivores among sites. In contrast to expectations, herbivore biomass was highest at sites with high predator biomass, low structural complexity, and low benthic productivity. Rather, the highest biomass of herbivores was associated with shallow, tidally emergent, productive reef flats located adjacent to steep vertical walls ("drop‐offs"). The emergent nature of this neighboring habitat precluded occupation by territorial fishes and multiple species of herbivores were observed to make foraging runs into this habitat once tidally inundated. We hypothesize that this habitat configuration provides an important cross‐habitat resource subsidy. Multivariate ordination and permutation of herbivore communities revealed strong evidence for biogeographic partitioning throughout the archipelago (western, southwestern, inner eastern, and outer eastern clusters), contributing to an emerging picture that the habitat heterogeneity of seascapes can overwhelm the effects of conventional top‐down and bottom‐up structuring of herbivory on coral reefs.